Characterizing Emotion Recognition and Theory of Mind Performance Profiles in Unaffected Siblings of Autistic Children - Uljarević, Mirko; Bott, Nicholas T.; Libove, Robin A.; Phillips, Jennifer M.; Parker, Karen J.; Hardan, Antonio Y. (Frontiers in Psychology, 2022)
Emotion recognition skills and the ability to understand the mental states of others are crucial for normal social functioning. Conversely, delays and impairments in these processes can have a profound impact on capability to engage in, maintain, and effectively regulate social interactions. Therefore, this study aimed to compare the performance of 42 autistic children (Mage= 8.25 SD= 2.22), 45 unaffected siblings (Mage= 8.65, SD= 2.45), and 41 typically developing (TD) controls (Mage= 8.65, SD= 2.45) on the Affect Recognition (AR) and Theory of Mind (TOM) subtest of the Developmental Neuropsychological Assessment Battery. There were no significant differences between siblings and TD controls. Autistic children showed significantly poorer performance on AR when compared to TD controls and on TOM when compared to both TD and unaffected siblings. An additional comparison of ASD, unaffected sibling and TD control subsamples matched on full-scale IQ, revealed no group differences for either AR or TOM. AR and TOM processes have received less research attention in siblings of autistic children and remain less well characterized. Therefore, despite limitations, findings reported here contribute to our growing understanding of AR and TOM abilities in siblings of autistic children and highlight important future directions.